4‐Fluorophenyl 3‐nitro‐2‐pyridinesulfenate as a practical protecting agent for amino acids. (15th February 2018) - Cui, Yan; Rentier, Cédric; Taguchi, Akihiro; Takayama, Kentaro; Taniguchi, Atsuhiko; Hayashi, Yoshio
Abstract : We report a new protecting agent (1, Npys‐OPh( p F)) for 3‐nitro‐2‐pyridine (Npy) sulfenylation of amino, hydroxy, and thiol functional groups. Several Npys phenoxides were synthesized from Npys chloride (Npys‐Cl) and phenols in the presence of base in 1‐step reaction, and their ability for Npy‐sulfenylation was evaluated. As a result, 1 was selected as a new Npy‐sulfenylation agent with advantages including improved physicochemical stability, more controllable reactivity, and easier handling than the conventional protecting agent Npys‐Cl. Abstract : We developed a new protecting reagent, 4‐fluorophenyl 3‐nitro‐2‐pyridinesulfenate, Npys‐OPh( p F), for Npy‐sulfenylation of amino, hydroxy, or thiol groups. This reagent has advantages including superior physicochemical stability, more controllable reactivity, and easier handling than conventional protecting agent Npys‐Cl.